Evaluation of Malignancy Risk of Ampullary Tumors Detected by Endoscopy Using 2-[ 18 F]FDG PET/CT - Chuang, Pei-Ju; Wang, Hsiu-Po; Tien, Yu-Wen; Chin, Wei-Shan; Hsieh, Min-Shu; Chen, Chieh-Chang; Hong, Tzu-Chan; Ko, Chi-Lun; Wu, Yen-Wen; Cheng, Mei-Fang (Korean journal of radiology, 2024)
We aimed to investigate whether 2-[ F]fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (2-[ F]FDG PET/CT) can aid in evaluating the risk of malignancy in ampullary tumors detected by endoscopy. This single-center retrospective cohort study analyzed 155 patients (79 male, 76 female; mean age, 65.7 ± 12.7 years) receiving 2-[ F]FDG PET/CT for endoscopy-detected ampullary tumors 5-87 days (median, 7 days) after the diagnostic endoscopy between June 2007 and December 2020. The final diagnosis was made based on histopathological findings. The PET imaging parameters were compared with clinical data and endoscopic features. A model to predict the risk of malignancy, based on PET, endoscopy, and clinical findings, was generated and validated using multivariable logistic regression analysis and an additional bootstrapping method. The final model was compared with standard endoscopy for the diagnosis of ampullary cancer using the DeLong test. The mean tumor size was 17.1 ± 7.7 mm. Sixty-four (41.3%) tumors were benign, and 91 (58.7%) were malignant. Univariable analysis found that ampullary neoplasms with a blood-pool corrected peak standardized uptake value in early-phase scan (SUVe) ≥ 1.7 were more likely to be malignant (odds ratio [OR], 16.06; 95% confidence interval [CI], 7.13-36.18; < 0.001). Multivariable analysis identified the presence of jaundice (adjusted OR [aOR], 4.89; 95% CI, 1.80-13.33; = 0.002), malignant traits in endoscopy (aOR, 6.80; 95% CI, 2.41-19.20; < 0.001), SUVe ≥ 1.7 in PET (aOR, 5.43; 95% CI, 2.00-14.72; < 0.001), and PET-detected nodal disease (aOR, 5.03; 95% CI, 1.16-21.86; = 0.041) as independent predictors of malignancy. The model combining these four factors predicted ampullary cancers better than endoscopic diagnosis alone (area under the curve [AUC] and 95% CI: 0.925 [0.874-0.956] vs. 0.815 [0.732-0.873], < 0.001). The model demonstrated an AUC of 0.921 (95% CI, 0.816-0.967) in candidates for endoscopic papillectomy. Adding 2-[ F]FDG PET/CT to endoscopy can improve the diagnosis of ampullary cancer and may help refine therapeutic decision-making, particularly when contemplating endoscopic papillectomy.